ANALISIS PENINGKATAN WAKTU PELAYANAN PRODUKSI KENDARAAN BERMOTOR RODA DUA PADA PERUSAHAAN MANUFAKTUR - Hernadewita Hernadewita; Hendra Hendra (Politeknik Negeri Padang, 2004)
The consumption motorcycle is the high. This is because people need the transportation and which the transportation cost expensive (by Bus, Car). For the consummate to need people a motorcycle, manufacturing company to production motorcycle, to make product with low cost and fast cycle time. This is doing with the large production area or new fabrication. With the improve a cycle time is the design to automatic system production example: to make use of AGV, Escalator, Lift etc, can be minimize to cost production and large production area. Results the calculated, the minimize cycle time and its time can be use for area shipping.